The Late Neolithic Expansion: Ancient and new traditions 2350-1700 BC - Winther Johannsen, Jens (Danish Journal of Archaeology, 2023)
Although the Scandinavian Late Neolithic today is mainly defined by the introduction of bifacial flint work, particularly daggers, agricultural intensification must also be seen as a part of the Late Neolithic package, which developed under Bell Beaker-influence in Jutland around 2350 BCE. It is argued that the changes in subsistence led to a population increase, which was the background for the spread of the new Late Neolithic culture in Scandinavia. A delay in the introduction of the Late Neolithic in East Denmark is, among other things, reflected in the scarcity of Bell Beaker-related artefacts in the region. It is suggested that this must be understood on the background of old cultural differences between West and East Denmark.